A Guide to People Management Practices Focused on the Circular Economy: A Theoretical Approach - , Caroline Kühl Gennaro; , Alexandre Tadeu Simon; , Carlos Roberto Camello Lima (Archives of Current Research International, 2023)
Aims: The training and development of people is essential for the companies that want to adopt the Circular Economy, but little has been objectively discussed in the literature on the subject, leaving several gaps for research. Then, the main goal of this study is to identify the people management practices organizations must adopt for the circular economy to happen in their processes and businesses. Study Design: Literature review and analytical assessment. Place and Duration of Study: Estate of São Paulo, Brazil, companies, experts, and general literature, between June 2019 and July 2020. Methodology: The study used a theoretical approach to people management practices in the general context as well as in the context of the Circular Economy. Then, a subjective analysis of the interpretation was performed to find correspondence between standard requirements and Circular Economy practices. Finally, a conceptual model was created. Results: The Circular Economy was characterized as sustainable development, justifying the need for human resource management to be oriented toward the Circular Economy. It was shown that 20% of articles in the literature address the need for people management oriented towards the circular economy. The relationship of the thirty-one identified practices with the standard requirements was divided into four dimensions: Organizational Culture; People Development; Leadership; and Team Development. A conceptual model was built based on the identified practices and classified into the four dimensions. Conclusion: The leading practices that best contribute to the Circular Economy context are divided into four dimensions and are recommended to be adopted for the successful transition to the Circular Economy. This research contributes to the human resources management in organizations transitioning to a Circular Economy and fills a gap in the development of people for such transition. Academically, it presents a contribution to the studies of people management in the context of Circular Economy for the changing organizations.